Classic paroxysmal nocturnal hemoglobinuria: A puzzling case of hemolytic anemia without cytopenia - Majed Abdul Basit Momin; Seema Afroze; G. Vamshi Krishna Reddy; Rahul Dev Singh Rathore (Iraqi Journal of Hematology, 2025)
Paroxysmal nocturnal hemoglobinuria (PNH) is an uncommon acquired complement-mediated hemolytic anemia characterized by continuous destruction of red blood cells leading to dark red or black colored urine. A 42-year-old man has been experiencing recurring jaundice, gastrointestinal discomfort, and high-colored urine for the past 2 years. His hemogram and antiglobulin tests were normal. The hemolytic anemia workup revealed reticulocytosis, hemoglobinuria, urine hemosiderin, elevated indirect bilirubinemia, and extremely low haptoglobin. A high index of suspicion for PNH prompted the laboratory physician to do flow cytometry, which confirmed the diagnosis of classical PNH. Here, we discuss a case of PNH that remained undiagnosed for years, detailing how we successfully identified a rare and confusing case of hemolytic anemia without cytopenia.